Production Flow valuation through VSM modeling: An industry case study (2017)
A special combination of lean methodologies and modeling of industrial processes has been increasingly used in the last decade between University and Industry. With lower costs, knowledge in lean tools and innovation in simulation packages, manufacturing has improved its practices in the flow of their processes detecting aggregate value. The research team describes a case in which a glove manufacturing production line and its Value Stream Mapping are simulated at the same time. The purpose of this work is to identify potential benefits such as reducing waste, improving lead time, resource optimization, reduced WIP and increasing throughput by simulation, applied to a real case industry. The modeling of the process and its VSM as a visual tool, highlight waste and hidden sources of the same through the variables and their behavior in the development of the simulation. Via a first simulation, the current process status is diagnosed. Then, using LEAN-manufacturing tools, a proposed VSM model is designed, which, through indicators and plots, shows the elimination of the causes of waste and improvements of this process.